Optimalisasi Kinerja Guru melalui Manajemen Sekolah dan Budaya Organisasi di Kepulauan Meranti - Syah, Syahrial; Achmad Kurniady , Dedi; Yuniassih , Tjuju; Prihatin, Eka; Supiani (BRILIANT: Jurnal Riset dan Konseptual, 2025)
This study examines the impact of school management, organizational culture, and workload on junior high school teachers' performance in Meranti Islands Regency. Using a quantitative approach, this study involved 135 civil servant teachers from 41 junior high schools as the sample. Data were collected through questionnaires and analyzed using regression to examine the relationship between the independent variables (school management, organizational culture, workload) and the dependent variable (teacher performance). The results of the analysis show that simultaneously, the three independent variables have a significant effect on teacher performance. The calculated F value (8.945) is greater than the F table (2.67), with a significant value of 0.000 <0.05. The null hypothesis is rejected and the alternative hypothesis is accepted, indicating a significant impact of the three variables on the performance of junior high school teachers in Meranti Islands Regency. This study was limited to a population of junior high school civil servant teachers in Meranti Islands Regency, so the results may not be generalizable to other regions or employment statuses. The findings have practical implications for school managers and education policy makers to improve teacher performance through improved school management, organizational culture, and effective workload management.